The Experience of Sexual Needs Fulfilment for People Who Life With HIV/AIDS Partners - I Gede Nyoman Ardi Supartha; I Wayan Surka; I Gusti Kadek Agus Dwi Putra (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2017)
Introduction: People with HIV/AIDS infected partners does not mean they should stop their sexual activities. Sexual needs fulfilment required commitment and support from their partners consider that the need of the willingness to gained the intimacy. The aim of the research to describing the people experienced in the sexual fulfilment with HIV/AIDS partners. Methods: This research applied descriptive phenomenology qualitative as the method, with in-depth interviews of 8 people with HIV/AIDS partners at Spirit Paramacitta Foundation, Denpasar. Results: Through the thematic analysis with the Colaizzi procedure, found 4 themes that illustrate the experience of fulfilling the sexual needs. The themes are: (1) The Declining of Sexual Relations Quantity and Quality as the Impact of The Changes of Partners Positive HIV Status, (2) Internal Conflicts Emerging in Responding to Sexual Assault, (3) Form of Sexual Activities Adaptation as the Impact of The Changes of Partners Positive HIV Status, (4) The Efforts to Increasing Sexual Quality. Conclusions: The role of the counselor in providing information related to safe sexual relationships is a solution that can overcome the fears and doubts of serodiscordant couples for sexual intercourse.